2023
DOI: 10.1186/s12872-023-03203-0
|View full text |Cite
|
Sign up to set email alerts
|

HOTAIR regulates SIRT3-mediated cardiomyocyte survival after myocardial ischemia/reperfusion by interacting with FUS

Abstract: Background Myocardial ischemia/reperfusion (I/R) contributes to serious myocardial injury and even death. Therefore, prevention and mitigation of myocardial I/R is particularly important. LncRNA HOTAIR has been reported to be implicated in myocardial I/R progression. However, the detailed molecular mechanism of HOTAIR in cardiomyocyte was explored in myocardial I/R. Methods Firstly, cell model of myocardial I/R was established through hypoxia/reoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The latest research has indicated that the overexpression of lncRNA-HOTAIR inhibits the HG-induced GSDMD-mediated pyroptosis and inflammatory response in diabetic cardiomyocytes through the FUS/SIRT3 axis [103]. In addition, cardiomyocyte damage caused by hypoxia/reoxygenation (H/R) can be alleviated by the overexpression of HOTAIR or SIRT3, thereby promoting cell viability and decreasing LDH levels [104]. All the above studies suggest that lncRNA plays a crucial role in cardiovascular disease by regulating the FUS/SIRT3 axis.…”
Section: Lncrnasmentioning
confidence: 99%
“…The latest research has indicated that the overexpression of lncRNA-HOTAIR inhibits the HG-induced GSDMD-mediated pyroptosis and inflammatory response in diabetic cardiomyocytes through the FUS/SIRT3 axis [103]. In addition, cardiomyocyte damage caused by hypoxia/reoxygenation (H/R) can be alleviated by the overexpression of HOTAIR or SIRT3, thereby promoting cell viability and decreasing LDH levels [104]. All the above studies suggest that lncRNA plays a crucial role in cardiovascular disease by regulating the FUS/SIRT3 axis.…”
Section: Lncrnasmentioning
confidence: 99%